2003
DOI: 10.1038/sj.onc.1206675
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ErbB2 enhances ethanol-stimulated intracellular signaling and invasion of human mammary epithelial and breast cancer cells in vitro

Abstract: Both epidemiological and experimental studies indicate that ethanol is a tumor promoter and may promote metastasis of breast cancer. However, the molecular mechanisms underlying ethanol-mediated tumor promotion remain unknown. Overexpression of ErbB proteins in breast cancer patients is generally associated with poor prognosis. The ErbB proteins are a family of receptor kinases that include four closely related members: epidermal growth factor receptor (EGFR/ErbB1), ErbB2/neu, ErbB3, and ErbB4. Particularly, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 71 publications
9
79
0
Order By: Relevance
“…For example, it is shown that the status of growth factor receptor and intracellular signaling components determine cellular sensitivity to ethanol. 21,41 Despite the differential sensitivity, these cells respond to ethanol in a similar pattern. Furthermore, selective inhibitors of MMP-2 (SB-3CT and OA-Hy) eliminate ethanolstimulated invasion.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…For example, it is shown that the status of growth factor receptor and intracellular signaling components determine cellular sensitivity to ethanol. 21,41 Despite the differential sensitivity, these cells respond to ethanol in a similar pattern. Furthermore, selective inhibitors of MMP-2 (SB-3CT and OA-Hy) eliminate ethanolstimulated invasion.…”
Section: Discussionmentioning
confidence: 92%
“…60,61 ErbB2 has been shown to facilitate the invasion of breast cancer cells in vitro and in vivo. 21,[63][64][65] The status of ErbB2 expression in a given cell is critical in determining the cellular response to various exogenous stimuli. 21,66 -68 Overexpression of ErbB2 could result in autophosphorylation, which initiates intracellular signaling; it is suggested that ErbB2 controls stroma-toepithelium crosstalk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of ligand to these receptors induces stimulation of the ErbB tyrosine kinase receptors. Among the ErbB family members, ErbB2 is most directly related to the tumorigenesis of breast cancer (Ma et al, 2003). Approximately 30% of breast tumors show HER2 over-expression, which is often associated with a more aggressive, metastatic phenotype and worse prognosis of breast cancer (Slamon et al, 1987;Yarden, 2001).…”
Section: Her2mentioning
confidence: 99%